Discrepancy Evaluation Model on Certification Competency Test Implementation of Vocational High School - Sherly; Kisno; Yuniarto Mudjisusatyo; Saut Purba; Edy Dharma; Humiras Betty Marlina Sihombing (Jurnal Pendidikan dan Pengajaran, 2023)
Certification Competency test is one of the requirements of VHS graduates and the gap between theory and phenomenon in this test evaluation is rarely carried out. The objective of this study is to evaluate the implementation of Certification Competency Test of VHS. A thorough evaluative method with Discrepancy Evaluation Model (DEM) was implemented through observation, and document study. Then, a questionnaire was developed to collect the data from 13 VHS as the population and sample. The data analysed descriptively fell into some categories as the finding of this research such as design, installation, process, product shared very good achievement with score 31.53 (100%), 57.4 (88.51%), 39.64 (87.52%), and 43.87 (89.22%) respectively.  The overall score denoted very good category with average gained score 172.44 (91.32%). In conclusion, the certification competency exam requires more maximum improvement despite the recent achievement. Good cooperation is needed from all parties, such as the provincial level national exam implementers, schools, partner institutions, supervisors, parents/community and students so as to fulfill the gap so that the certification competency test results will be even better.